Sports-related concussion among high school athletes in West Central Florida. (7th October 2012) - Jang, S; Liller, KD; Konin, J; Morris, B; Wong, S
Abstract : Background: Sports concussion among children and adolescents has been recognised as an important public health concern. Research shows that these groups are at increased risk for Traumatic Brain Injury (TBI)-related issues such as delayed recovery and long-term sequelae. Aims/Objectives/Purpose: The purpose of this study was to collect and report concussion data from high school athletes enrolled in four public high schools in west-central Florida. Methods: Sports-related injury data (including concussion incidence) were collected from 9 August to 12 December 2010 utilising professional sports injury surveillance software. The surveillance system captured exposure and risk factor information of high school athletes. Four certified athletic trainers (ATCs) were hired by the Sports Medicine and Athletic Related Trauma (SMART) Institute of the University of South Florida to collect the data. The ATCs exported the information to the university once a week for analysis. Results/Outcome: There were 24 sports-related concussions reported during the data collection period. The majority of concussions took place during football competitions and practices (87.5%). The concussed athletes were mostly males (95.83%) and juniors (33.33%) followed by freshman (25%). The leading level of play for injury was varsity (66.67%) followed by junior varsity (JV) (33.33%). The leading concussion symptom was headache (21.59%) followed by dizziness/unsteadiness (15.91%) and sensitivity to light/visual disturbances (11.36%). The leading reported concussion time was 1–3 days (37.5%). Players returned to play mostly within 7–9 days (68.75%). Significance/Contribution to the Field: These data will serve to inform future research and practice to prevent concussions among high school athletes.